EDUKASI KADER TB TENTANG PROMOSI KESEHATAN PROGRAM TB PARU DI KOTA JAMBI TAHUN 2023 - Saquro, Abdan; Mustopa, Rd; Agraini, Agraini (BINAKES: Jurnal Pengabdian Kesehatan Masyarakat, 2023)
National TB control continues to intensify, accelerate, extensify and innovate programs, under President Jokowi, access to quality TB services has been increased, one of which is the Movement to Find a Treatment to Cure TB Disease (TOSS-TB) where all community health centers become Independent Community Health Centers, then there is a strengthening of the network. services with the community, then establishing and strengthening a referral system. Jambi City consists of 8 sub-districts, namely Kota Baru, South Jambi, Jelutung, Pasar Jambi, Telanaipura, Danau Teluk, Pelayangan and East Jambi, covering an area of ​​205.38 km2 with a total population of 417,507 people. The subdistrict with the largest area is South Jambi District (34.07 km2) while the subdistrict with the smallest area is Pasar Jambi District (4.02 km2). Health service facilities 17 hospitals, 20 health centers. Jambi City Regency Pulmonary TB Program Report in 2018 Case Detection Rate (CDR) for smear positive pulmonary TB was 30%, in 2019 it was 31% and in 2020 it was 30%.